Analysis of the structural, elastic constants, electronic, optical, dynamical, and thermodynamic in dicalcium silicate with various pressures. (April 2023) - Hou, Hai-Jun; Chen, Wen-Xuan; Zhu, Hua-Jun; Lu, Xiao-Wang; Zhang, Shun-Ru; Zhang, Qin-Fang
Abstract: Theoretical simulation plays an increasingly important role in obtaining the structural characteristics and performance of materials. Using first-principles calculations, the structural, anisotropic elasticity, electronic properties, dynamics, and thermodynamics of Dicalcium Silicate (γ-Ca2 SiO4 or γ-C2 S) under a pressure of 0–10 GPa are studied. The optimized lattice constants and inter-atomic distances are consistent with other theoretical and experimental values, which shows that our simulation settings are reliable and give reasonable results. In addition to the structural data, we systematically studied the anisotropic elasticity, thermal conductivity, phonon, optical, and electronic properties of γ-C2 S. The anisotropy of three-dimensional(3D) and two-dimensional(2D) projected Bulk modulus and Young's modulus are systematically analyzed. The calculation results show that the γ-C2 S has mechanical stability, and the system has significant anisotropy. In addition, according to the density functional perturbation theory (DFPT), the infrared active and inactive vibration modes are given and analyzed. This study shows that γ-C2 S is also dynamically stable. Finally, through the phonon method and the quasi-harmonic Debye model method, heat capacity C v and entropy S are calculated and analyzed in the temperature range of 0–700 K. We also found that the present work can give a reference to those not to be experimentally investigated. Highlights: The mechanical properties were all systematically calculated and analyzed. The elastic anisotropy of γ-Ca2 SiO4 increased with increasing pressure. The results reveal that γ-Ca2 SiO4 can be mechanically and dynamically stable.